(untitled) (Palíndromo, 2023)
This article analyzes the multiplicity of terms adopted to characterize collaborative and participatory artistic practices, therefore, it lists definitions that emerged from the 1990s and their particularities. This study is justified both by suggesting a mapping and a chronological organization of these studies and these ways of working in the field of art, as well as for valuing the specificities of these theoretical approaches, distinguishing them: new genre of public art, art of the margins, community-based art, relational aesthetics, dialogic art, interventionist art, socially engaged art, emergence aesthetics, social turn, participatory art, pedagogical turn and collaborative art. Among the objectives of this research is to reflect on the approach of the public with this trend of contemporary production, encouraged by several authors located in different local contexts. For this, a qualitative approach and a bibliographic survey were established, dealing with contributions from the main theorists, such as: Suzanne Lacy, (1994), Bruce Barber, (1996), Deidre Williams (1997), Nicolas Bourriaud (1998) Grant H. Kester (1998, 2004, 2011, 2012), Jonas Ekeberg (2003), Claire Bishop (2006, 2008, 2012) e Reinaldo Laddaga (2006).